Evaluation of the efficacy and safety of Capsule Longvida® Optimized Curcumin (solid lipid curcumin particles) in knee osteoarthritis: a pilot clinical study - Gupte PA; Giramkar SA; Harke SM; Kulkarni SK; Deshmukh AP; Hingorani LL; Mahajan MP; Bhalerao SS (Dove Medical Press, 2019)
Poonam Ashish Gupte,1 Shital Ashok Giramkar,1 Shubhangi Mandar Harke,1 Sneha Keshav Kulkarni,1 Amol Panjabrao Deshmukh,2 Lal Lachhmandas Hingorani,2 Madhavi Prabhakar Mahajan,3 Supriya Sudhakar Bhalerao11Obesity Diabetes lab, Interactive Research School for Health Affairs (IRSHA), Bharati Vidyapeeth Deemed University Campus, Pune, Maharashtra, India; 2Research and Development Department, Pharmanza Herbals Pvt. Ltd., Dharmaj, Gujrat, India; 3College of Ayurved, Bharati Vidyapeeth Deemed University Campus, Pune, Maharashtra, IndiaPurpose: Osteoarthritis is the single most common cause of disability in older adults with an estimated 10% to 15% prevalence in individuals above 60 years. The contemporary medications include nonsteroidal anti-inflammatory drugs acetaminophen, cyclooxygenase-2 inhibitors, and surgical interventions. In view of safety issues regarding their longterm use, necessitating search for effective and safe alternatives, we evaluated Capsule Longvida®, Optimized Curcumin prepared using solid lipid curcumin particles (SLCP) technology in patients with knee osteoarthritis.Patients and methods: Eligible patients fulfilling American College of Rheumatology Criteria were randomized to SLCP group (400 mg twice daily delivering 80 mg of curcumin per capsule) or Ibuprofen with placebo group (400 mg each once daily) for 90 days. The Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and the Visual Analog Scale (VAS) were used for clinical assessment of knee pain and function. Degree of knee flexion and swelling were also noted. Blood biochemistry included hemogram, blood urea, creatinine, Random blood sugar and inflammatory markers viz. PGE2, TNF α, IL6, IL1β and LTB4 while urine examination included degenerative marker CTX II. The parametric data was analyzed using unpaired t test while non-parametric data was analyzed using Friedman’s test or Mann Whitney t test as applicable. A level of p<0.05 was considered as statistically significant.Results: Out of 50 recruitments, 25 from the Ibuprofen group and 17 from the SLCP group completed the study with significant improvements in VAS and WOMAC scores indicating comparable efficacy of SLCP in alleviating pain with Ibuprofen. None of the markers displayed significant changes. Except one withdrawal in the study group due to rash and itching, the study drug was found safe.Conclusions: SLCP in a dose of 160 mg daily was found to be effective and safe in alleviating symptoms in patients suffering from knee osteoarthritis when administered for 90 days.Keywords: inflammation, Ibuprofen, solid lipid curcumin particles (SLCP), WOMAC score